Psychological Impact and Support Strategies in mothers with Tuberculosis History: Dampak Psikologis dan Strategi Dukungan pada Ibu dengan Riwayat Tuberkulosis - Erianti, Anggie; Azizah, Nurul (Indonesian Journal on Health Science and Medicine, 2024)
This case study examines the psychological impact on Mrs. N, a mother of a 1-year-old child diagnosed with pulmonary tuberculosis. Mrs. N experiences significant anxiety and fear due to concerns about her child's health and societal perceptions. Data was collected through home visits and interviews, and interventions included following medical advice, practicing patience, and using the Bansons relaxation method. Support from her husband and family proved crucial in alleviating her psychological distress. The study highlights the importance of comprehensive support systems for mothers coping with a child's serious illness.. Highlights: Maternal Anxiety: N fears societal responses to child's tuberculosis diagnosis. Interventions: Follow medical advice, practice patience, use Bansons relaxation method. Support System: Husband and family support crucial for psychological well-being. Keywords: Pulmonary tuberculosis, maternal anxiety, psychological impact, Bansons relaxation, family support